LEADERSHIP STYLES AND THEIR EFFECTS ON EMPLOYEES’ TURNOVER IN PRIVATE BUSINESSES OF THE AUSTRIAN MARKET - Bitzikou, Eleftheria (Digital Repository of Theses, 2023)
According to existing research, leadership styles play an important role on the employee turnover. The employee turnover is a very important factor that affects the financial situation of a business. This research aims to explore whether the Leadership styles affect the employee turnover in private businesses in the Austrian Market. This research was conducted by a literature review and a survey. The data analysis for this study was carried out using quantitative statistical methods. Questionnaires were sent to all the participants, were completely anonymous and no personal data were neither asked or saved in any way. The questionnaires feature 6 questions aiming to collect robust information by the use of close-ended, multiple-choice questions, providing quantitative data for analysis The data received from the questionnaires were sufficient to perform the research and were statistically analysed in order to examine if there is a link between the employee turnover and the leadership styles in private Austrian businesses. The findings of this research might be useful to fill the gap in understanding the role of leadership styles on employee turnover. This research was conducted for private Austrian business and has yielded results relevant to the influence of the leadership styles on the employee turnover on a country with low unemployment rate as well as good unemployment benefits. From these facts it could be safe to assume that the responses of the participants, thus the results of this research were mainly genuine and not influenced by factors such as e.g., financial instability or fear of unemployment.